Characteristics and Protein Binding Affinity of Condensed Tannins in Leucaena Species - Khamseekhiew, Bodee (2006)
Four experiments were conducted to evaluate the role and metabolism of phenolic compounds particularly condensed tannins (CT) in selected Leucaena species [Leucaena-hybrid Bahru; LLB, Leucaena-hybrid Rendang; LLR, Leucaena leucocephala-local; LLL and Leucaena leucocephala-Subang; LLS] using in vitro and in vivo studies. The occurrence of phenolic compounds in the above Leucaena and their correlations with in vitro gas production and degradability were investigated in the first experiment. The results showed that hybrid LLR had the highest CT content, resulting in the lowest in vitro gas production and degradability among the four species tested. Within shoot of similar age, the in vitro gas production and N degradability were negatively correlated to CT content, but such relationship were not detected if shoot samples of different age groups were pooled. The above findings indicated that concentration of tannins may not be the sole factor affecting nutrient utilisation. Results of the second experiment showed that there were no significant differences in the total phenolics and extractable CT contents, gas production and DM degradability for the samples dried at temperature of 45° C as compared to the standard freeze drying procedure. The present results indicated that where facilities for freeze drying are not available, drying at 45° C would serve as an option for measurement of the content of tannins as well as the effects on the in vitro. Drying at 60 °C and the addition of polyethylene glycol (PEG) reduced the adverse effect of CT. When treated at 60° C, the in vitro gas production and N degradability increased by about 24.7 and 26.2 %, respectively. With the addition of PEG, the corresponding values were 42.6 and 22.6%, respectively. Once again, DM degradability was highest in the local LLL (63.3%), followed by the hybrids LLB (58.9%) and LLR (55.1%), suggesting the depression of DM degradability of the hybrids as the results of their higher tannin contents. In the third experiment, CT were isolated and purified from three Leucaena species to evaluate differences in their biological binding affinity (astringency) and molecular weight. The study showed that the phenolics precipitation protein (PPP) value for LLR and LLB were significantly higher than that of LLL. Similarly, LLR and LLB also exhibited higher binding affinity than LLL, with the values of 0.13, 0.72 and 1.32 mg CT mg-1 bovine serum albumin (BSA), respectively. The above findings provide further explanation for the stronger adverse effect of CT of the hybrid species as compared to the local variety. Although majority of CT purified from the hybrid species was made of larger molecules than those of the local Leucaena, thus once again support the hypothesis that CT of stronger binding affinity are of larger molecular weight. The conclusion based on the current results is not conclusive and need further studies.The last Chapter consisted of two in vivo experiments. The results showed that inclusion of PEG in diets improved DM and N digestibilities, N retention, rumen ammonia (NH3) as well as microbial N supply in sheep, with no significant differences on animal performance when the two types of Leucaena species (hybrid and local) were compared.